Insecta of Tungonan, Kananga, Leyte - Pastor, Trinidad M. (1967)
In a joint venture with San Carlos University, the Divine Word University undertook its first scientific expedition to Tungonan, a barrio of Kananga, Leyte. The expedition had the following objectives:
1. To start an entomological collection for the University Biology Department.
2. To survey insect densities on mid-mountain elevations and in forest areas.
3. To observe the effects of volcanic environment on the ecology of insects.
Keywords: Insects -- Tongonan (Leyte)